2020
DOI: 10.1111/1440-1681.13241
|View full text |Cite
|
Sign up to set email alerts
|

Exosomal miR‐103a‐3p ameliorates lipopolysaccharide‐induced immune response in BEAS‐2B cells via NF‐κB pathway by targeting transducin β‐like 1X related protein 1

Abstract: Abnormal immune response contributes to pathophysiology of pneumonia and is recognized as a main factor for high incidence rate in children. The association between exosomes and inflammation has been reported in diverse cell types and diseases. The current study focuses on exploring the effects of exosomal miR‐103a‐3p on lipopolysaccharide (LPS)‐induced inflammation, and investigates the underlying mechanisms. We proved that miR‐103a‐3p was lowly expressed in blood samples of pneumonia patients and LPS‐induced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 40 publications
(78 reference statements)
0
9
0
Order By: Relevance
“…A recent study also reported that miR-103a-3p was upregulated in EVs during ZIKV infection ( Tabari et al, 2020 ). MiR-103a-3p has multiple functions involved in the regulation of inflammation, immune response, and development of a variety of cancers ( Geng et al, 2014 ; Hu et al, 2018 ; Lu et al, 2019 ; Li et al, 2020 , 2021 ). However, to date, the effect of miR-103a-3p on the regulation of pathogen infection has not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study also reported that miR-103a-3p was upregulated in EVs during ZIKV infection ( Tabari et al, 2020 ). MiR-103a-3p has multiple functions involved in the regulation of inflammation, immune response, and development of a variety of cancers ( Geng et al, 2014 ; Hu et al, 2018 ; Lu et al, 2019 ; Li et al, 2020 , 2021 ). However, to date, the effect of miR-103a-3p on the regulation of pathogen infection has not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…miRNAs including miR-124, miR-146a, and miR-181b-5p are critical for regulating microglial development and activation. [ 36 38 ] miR-103a-3p is linked with cancer progression [ 39 41 ] but also performs a variety of physiological functions across multiple biological processes, including immunity [ 42 ] and oxidative stress. [ 43 ] miR-103a-3p is significantly downregulated in LPS-treated lung cells; miR-103a-3p overexpression reduces LPS-induced inflammation, [ 42 , 44 ] showing a protective effect of these non-coding RNA molecules against inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…[ 36 38 ] miR-103a-3p is linked with cancer progression [ 39 41 ] but also performs a variety of physiological functions across multiple biological processes, including immunity [ 42 ] and oxidative stress. [ 43 ] miR-103a-3p is significantly downregulated in LPS-treated lung cells; miR-103a-3p overexpression reduces LPS-induced inflammation, [ 42 , 44 ] showing a protective effect of these non-coding RNA molecules against inflammation. [ 43 ] The contribution of miR-103a-3p to neurological diseases, however, has rarely been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of exosomal miR-103a-3p attenuates inflammation by regulating immune response via transducing β-like 1X related protein 1/NF-κB signaling pathway. 559 …”
Section: The Roles Of Exosomal Ncrnas In Human Diseasesmentioning
confidence: 99%